Copper‐Catalyzed Intermolecular Carboetherification of Unactivated Alkenes by Alkyl Nitriles and Alcohols1. Issue 18 (3rd March 2015) - Chatalova‐Sazepin, Claire; Wang, Qian; Sammis, Glenn M.; Zhu, Jieping
Abstract A three‐component carboetherification of unactivated alkenes has been developed allowing the rapid building of complexity from simple starting materials. A wide range of α‐substituted styrenes underwent smooth reactions with unactivated alkyl nitriles and alcohols to afford γ‐alkoxy alkyl nitriles with concomitant generation of a quaternary carbon center. A radical clock experiment provided clear‐cut evidence that the reaction proceeds through a tertiary alkyl radical intermediate.